Cardiovascular risk profiles and stress echocardiography results in patients with hypertensive response to exercise - E. A. Karev; E. G. Malev; A. Yu. Suvorov; S. L. Verbilo; M. N. Prokudina (Российский кардиологический журнал)
Aim. To compare markers of high cardiovascular risk and stress echocardiography results depending on the type of blood pressure (BP) response to exercise in patients without obstructive coronary artery disease.Material and methods. Our single-center cross-sectional study included 96 patients without hemodynamically significant coronary artery stenosis according to coronary angiography or multislice computed tomography angiography. All patients underwent physical examination, cardiovascular risk stratification, electrocardiography, extracranial cerebrovascular ultrasound, echocardiography, treadmill exercise stress echocardiography.Results. According to the test results, the patients were divided into groups with a hypertensive response (n=41) and a normal response to exercise (n=55). Patients with hypertensive response to exercise had significantly higher values of left ventricular mass index (100,0 (90,0; 107,0) g/m2 vs 76,0 (68,0; 91,0) g/m2, p<0,0000001) and left atrial volume index (36,7 (32,0; 46,0) ml/m2 vs 29,7 (26,3; 32,0) ml/m2, p=0,000003). There was also a higher level of cardiovascular SCORE risk (5,0 (2,0; 6,0) vs 2,0 (1,0; 3,0), p=0,004); patients more often had associated clinical conditions (36,6% vs 12,7%, χ2=7,57, p=0,006) and left ventricular diastolic dysfunction (39,02% vs 78,18%, χ2=15,21, p=0,0001). Pathological BP increase during stress echocardiography was associated with worse exercise tolerance (7,4 (5,6; 10,0) METs vs 10,2 (8,4; 11,95) METs, p=0,000041) and more frequent transient regional contractility impairment (46,34% vs 1,8%, p<0,00001), mainly of the lateral and inferior left ventricular walls.Conclusion. Despite the absence of coronary artery stenosis, patients with hypertensive response to exercise are significantly more likely to have markers of high cardiovascular risk and require more careful monitoring of risk factors. Also, the hypertensive response to exercise is associated with more frequent regional contractility impairment even without coronary artery stenosis.